Changes in and predictors of pain characteristics in patients with head and neck cancer undergoing radiotherapy. Issue 5 (May 2015) - Astrup, Guro Lindviksmoen; Rustøen, Tone; Miaskowski, Christine; Paul, Steven M.; Bjordal, Kristin
Abstract : Abstract: Pain is a common symptom in patients with head and neck cancer (HNC) that is associated with significant decrements in physical and psychological functioning. Only 4 studies have evaluated for changes in and predictors of different pain characteristics in these patients. In this longitudinal study of patients with HNC, changes in pain intensity (ie, average pain, worst pain), pain interference with function, and pain relief were evaluated from the initiation of radiotherapy and through the following 6 months. Hierarchical linear modeling was used to evaluate for changes over time in these 4 pain characteristics, as well as to identify predictors of interindividual variability in each characteristic. Overall, pain intensity and interference with function scores were in the mild-to-moderate range, while pain relief scores were in the moderate range. The occurrence of pain, as well as scores for each pain characteristic, increased from the initiation to the completion of radiotherapy, followed by a gradual decrease to near pretreatment levels at 6 months. However, interindividual variability existed in patients' ratings of each pain characteristic. Predictors of more severe pain characteristic scores were more comorbidities, worse physical functioning, not having surgery before radiotherapy, difficulty swallowing, mouth sores, sleep disturbance, fatigue, more energy, and less social support. Patients with more depressive symptoms had better pain relief. Although some of the predictors cannot be modified (eg, occurrence of surgery), other predictors (eg, symptoms) can be treated. Therefore, information about these predictors may result in decreased pain in patients with HNC. Abstract : Patients with head and neck cancer report a high prevalence of pain. Several characteristics can be used to identify patients at higher risk for pain.